KAJIAN REDESAIN KAWASAN GOR SEGIRI SAMARINDA PENDEKATAN PADA LANDMARK KOTA - Hatta Musthafa Adham Putra; Tumingan Tumingan; Joko Suryono (Jurnal Riset Inossa, 2022)
The Segiri Sports Arena is an area that provides sports facilities for the people of Samarinda City and its surroundings. Various sports facilities are available, but as the city of Samarinda develops, the area has turned into a multifunctional area due to the activities carried out by the community. This transformation has caused the Segiri GOR area to look slum. In order to restore the main function and accommodate all these multifunctional activities with a better arrangement, as well as efforts to make a redesign that can become a landmark of the City of Samarinda, research is needed on the study of the redesign of the Segiri Samarinda GOR area with an approach to city landmarks. The parameters used are the landmarks and the characteristics of the sport building. This research would be useful for the government to improve and accommodate various functions of community needs for sports areas, and present new city landmarks for Samarinda City. This Samarinda City landmark brings elements of the distinctive character of the City of Samarinda in the form of the building.